2014
DOI: 10.1016/j.wem.2013.09.008
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Ivermectin to Kill Ixodes Scapularis Ticks Feeding on Humans

Abstract: There were a high number of ticks that died in both groups but the data do not support our hypothesis that ivermectin can kill I scapularis. The study was not designed to determine whether it could prevent the transmission of tick-borne illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…In our previous study, it was demonstrated that IVM and AVM of the AVM family not only inhibited the proliferation of glioma cells via evoking apoptosis but also induced autophagy in glioma cells ( 21 , 48 ). Furthermore, IVM has been used to treat filariasis and kill ixodesscapularis ticks feeding on humans ( 49 ). In the present study, DRM, a more effective and less toxic drug from the AVM family, was used to treat GBM.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, it was demonstrated that IVM and AVM of the AVM family not only inhibited the proliferation of glioma cells via evoking apoptosis but also induced autophagy in glioma cells ( 21 , 48 ). Furthermore, IVM has been used to treat filariasis and kill ixodesscapularis ticks feeding on humans ( 49 ). In the present study, DRM, a more effective and less toxic drug from the AVM family, was used to treat GBM.…”
Section: Discussionmentioning
confidence: 99%
“…70 However, in a case series, tick removal with forceps was associated with a lower rate of spirochetal and rickettsial infections. 71 Passive methods such as application of petroleum jelly, fingernail polish, 70% isopropyl alcohol, or a hot kitchen match, 67,72 local infiltration of anesthetics, 73 and administration of oral ivermectin 74 failed to exhibit any efficacy in encouraging tick detachment. Overall, mechanical removal is largely accepted by experts, 75 and forceps removal has been endorsed by the CDC (Figure 5) 8 ; however, to date no professional organization has adopted strong practice guidelines regarding optimal tick removal techniques.…”
Section: Tick Removalmentioning
confidence: 99%
“…Nowadays, IVM is used mainly as an oral medication in the primary treatment of onchocerciasis, lymphatic filariasis, and strongyloidiasis infections, all caused by different nematode species ( Turner and Schaeffer, 1989 ; Laing et al., 2017 ). IVM also affects arthropod ectoparasites, being used in the treatment of scabies ( Thomas et al., 2015 ), ticks ( Sheele et al., 2014 ), and head lice ( Devore and Schutze, 2015 ).…”
Section: Introductionmentioning
confidence: 99%